Nietzsche : Beginner's Guide - Wicks, Robert (UK Oneworld Publications, 2002)
Often quoted, influential, and highly divisive, Nietzsche remains an enigma long after his death. This clear primer moves deftly through the controversy to examine the philosopher$1 (Bs work in the context of his tumultuous childhood and Christian upbringing. Discussing his infamous declaration that (3z(BGod is dead(3y(B, his posthumous association with Nazism, and his criticisms of conventional morality, this book is the ideal introduction to the much debated thinker and his extensive legacy.s
Includes Inden and Biblioigraphy.
Keywords: History -- Nietzsche, Friedrich Wilhelm, 1844-1900